On the perception of science by Poles: corpus-based descriptive study of public consultation data - Dzimińska, Małgorzata; Grabowski, Łukasz; Krzewińska, Aneta; Warwas, Izabela (Papers in Linguistics, 2023)
This descriptive study, conducted using corpus linguistic research methods, examines the ways the Polish public perceives science. Starting from selected assumptions of Critical Discourse Analysis and the Linguistic Picture of the World, whereby language is seen primarily as a social practice and as a carrier of knowledge, opinions, beliefs and attitudes, we analyse the data obtained during public consultations on science communication which were held in 2019 in Poland, as part of the CONCISE project. The combined quantitative and qualitative analyses focus on selected collocations of a high-frequency noun nauka (‘science’) and aim to identify patterns of reference and agency within the discourse. The findings revealed citizens’ expectations concerning science, including its clarity, accessibility, understandability, visibility and credibility.